Brain machine interface for physically retarded people using colour visual tasks - Pandiyan, Paulraj Murugesa, Prof. Dr. (IEEE Conference Publications, 2014)
Proceeding of The 6th International Colloquium on Signal Processing & Its Applications (CSPA 2010) at Melaka, Malaysia on 21 May 2010 through 23 May 2010. Link to publisher's homepage at http://ezproxy.unimap.edu.my:2080/Xplore/dynhome.jsp?tag=1